2002
DOI: 10.1212/wnl.58.6.928
|View full text |Cite
|
Sign up to set email alerts
|

Selective reduction of N -acetylaspartate in medial temporal and parietal lobes in AD

Abstract: Background-Both AD and normal aging cause brain atrophy, limiting the ability of MRI to distinguish between AD and age-related brain tissue loss. MRS imaging (MRSI) measures the neuronal marker N-acetylaspartate (NAA), which could help assess brain change in AD and aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
74
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 40 publications
8
74
0
6
Order By: Relevance
“…In the hippocampus, a relatively small structure in the magnetically inhomogeneous environs of the petrous temporal bone, localized short echo time MRS has measurement errors of 20% or more, sufficient to mask any biological differences in NAA associated with Alzheimer disease. On the other hand, use of the more robust MRS technique, long echo time chemical shift imaging confirms a loss of NAA from the hippocampus in Alzheimer disease which is directly proportional to the volume loss of that structure (Schuff et al, 2002). Schuff and colleagues have reported that NAA reductions and volume loss made independent contributions to the correct discrimination of Alzheimer disease patients from controls, with a better than 80% correct diagnosis using NAA declines alone, which improved to 90% when NAA loss and volume reductions were combined (Schuff et al, 2006).…”
Section: Magnetic Resonance Spectroscopy and Imaging Of Naamentioning
confidence: 96%
“…In the hippocampus, a relatively small structure in the magnetically inhomogeneous environs of the petrous temporal bone, localized short echo time MRS has measurement errors of 20% or more, sufficient to mask any biological differences in NAA associated with Alzheimer disease. On the other hand, use of the more robust MRS technique, long echo time chemical shift imaging confirms a loss of NAA from the hippocampus in Alzheimer disease which is directly proportional to the volume loss of that structure (Schuff et al, 2002). Schuff and colleagues have reported that NAA reductions and volume loss made independent contributions to the correct discrimination of Alzheimer disease patients from controls, with a better than 80% correct diagnosis using NAA declines alone, which improved to 90% when NAA loss and volume reductions were combined (Schuff et al, 2006).…”
Section: Magnetic Resonance Spectroscopy and Imaging Of Naamentioning
confidence: 96%
“…By utilizing MRS, reduced NAA and increased myo-inositol concentrations have been consistently found in the brain of AD patients compared to cognitively healthy elderly individuals and to be correlated to decline in cognitive performance (e.g. Chantal et al, 2002Chantal et al, , 2004Huang et al, 2001;Kantarci et al, 2004;Klunk et al, 1998;Jessen et al, 2000Jessen et al, , 2009Meyerhoff et al, 1994;Miller et al, 1993;Mohanakrishnan et al, 1997;Pfefferbaum et al, 1999a,b;Rose et al, 1999;Schuff et al, 2002;Watanabe et al, 2010). While NAA indicates loss of neuronal integrity, myo-inositol has been interpreted as a marker of gliosis (see discussion above).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…[17][18][19][20][21] The decrease of NAA or the NAA/creatine (Cr) ratio shows a regional variation in AD. [22][23][24] In patients with mild to moderate AD, NAA/Cr levels are lower than normal in the posterior cingulate gyrus, whereas they are normal in the medial occipital lobe, including in the visual cortex. 23 This regional pattern is in agreement with the distribution of the neurofibrillary pathology, and the associated neuron loss in people with mild to moderate AD, indicating that regional NAA/Cr levels are potential surrogates for disease progression.…”
mentioning
confidence: 99%